IC 6574 Milling Methods At The Balmat Mill Of The St. Joseph Lead Co., Balmat, St. Lawrence County, N. Y. - Introduction - John B. Knaebel (The National Institute for Occupational Safety and Health (NIOSH), 1932)
This paper, describing the milling operations of the St. Joseph Lead Co. at Balmat, N. Y., is one of a series of similar papers being prepared by the United States Bureau of Mines on practice at various mills in the United States, Canada, and Mexico. The company also operates a mine end mill at Edwards, 12 miles northeast of Balmat. Mining practice in the district, as exemplified at the Edwards mine, is described in another information circular of the Bureau of Mines.3 The writer gratefully acknowledges the generous cooperation of the company officials which made this investigation possible, and wishes to thank R. J. Mechin, manager, P. W. Wolf, mill superintendent, and F. G. Kuehl, assistant mill superintendent, for their helpful assistance. Especial thanks are due J. S. Brown, geologist, for supplying information on the characteristics of the ore, and to C. F. Jackson, principal mining engineer, U. S. Bureau of Mines, for helpful suggestions.